In this issue - Yamakawa T, Peter (2014)
We are pleased to introduce the 37th issue of the Journal of Economics, Finance and Administrative Science. The journal promotes research in the field of economics, finance, operations, management and supply chain management. This issue is very particular because it is the first edition with the inclusion of our journal in the database of Scopus, one of the most prestigious databases worldwide. By September 2014,the Scopu’s Content Selection & Advisory Board accepted our journal for inclusion in their database. Doi: http://dx.doi.org/10.1016/j.jefas.2014.11.001